Perkembangan Bisnis Food Trucks Di Kota Lhokseumawe - Juliana Putri, Juliana Putri (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2023)
The development of food trucks in the city of Lhokseumawe is increasingly lively with the increasing number of food trucks making business opportunities through food trucks an alternative way of doing business. The formulation of the problem in this research are: 1) How is the influence of capital on the development of the food truck business? 2) How does the location influence the development of the food truck business? This research is a type of field research with a quantitative approach with a sample of 30 people. This study uses a questionnaire with calculations using the liker scale. Based on the results of the study found that the capital and location variables significantly influence the development of the business of food truck traders in the city of Lhokseumawe thus H1 and H2 can be accepted, while for the hypothesized cost is concluded reject H3 and accept H0 because the value obtained is significantly positive while the hypothesis has a significant negative effect. Simultaneously obtained value can be concluded that the H0 accept Ha means that the independent variables (capital, location and cost) jointly affect the dependent variable (Business Development). Affected significantly.